The Burden of Early Childhood Caries in Canadian Children and Associated Risk Factors - Pierce, Andrew; Singh, Sarbjeet; Lee, JuHae; Grant, Cameron; Cruz de Jesus, Vivianne; Schroth, Robert J. (Frontiers in Public Health, 2019)
Introduction: Early childhood caries (ECC) is one of the important caries occurring in children under the age of six. ECC common in many population groups in Canada. Objective: The purpose of this review was to identify the burden of ECC in Canada, prevalence of ECC and its impact on childhood health, and associated risk factors for ECC. Methods: A systematic review was conducted to review published Canadian studies on ECC identified through searches of electronic databases. Databased searched included PubMed, Medline, Cinahl and the library catalogue of the University of Manitoba. Known publications on ECC that were not identified by the electronic search were also considered. Only the studies that reported the prevalence of ECC or caries in preschool aged children were considered. In-depth assessments were restricted to those studies that employed logistic regression analysis to investigate relationship between ECC and risk factors or nutritional status and quality of life. Results: A total of 36 studies were identified that related to ECC in Canadian children. Overall, 27 related to prevalence and 12 reported on risk factors, 4 related to the association between severe ECC and nutritional health and well-being, while only 1 related to the oral microbiome composition. Published studies reveal that anywhere from zero to 98% of children in Canada may be affected by ECC. Commonly identified risk factors include age, sex, socio-economic status, parental beliefs, family characteristics, debris/plaque and behavioural (oral health or feeding behaviours). Enamel hypoplasia also appears to be strongly associated with ECC. Conclusions: Many Canadian children are affected by ECC in the infant and preschool periods. ECC appears to be strongly associated with “social determinants of health”, child’s age at first dental visit, and parental beliefs about child’s oral health. Enamel hypoplasia is also a strong risk factor, but, unfortunately, not commonly assessed in studies on ECC in Canada. Multiple logistic regression should become standard practice to identify true risk factors for ECC as this methodology can help to control for confounders.